Tingkat kepuasan kelompok wanita tani terhadap kinerja penyuluh pertanian lapang - Zulkarnain; Supriyadi; Evi Karina; Rakhmiati; Etik Puji Handayani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
The purpose of the study was to determine the level of satisfaction of the female farmer group on the performance of the field extension workers. The sample consisted of 40 members of the women's farmer group Bina Pertain determined by the census technique. The analysis used is Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results obtained are the level of satisfaction of the female farmer group on the service attributes classified as satisfied. The level of importance of the service is greater than the level of performance of the field instructor, this indicates that the level of agricultural performance of the field extension worker has not met the expectations desired by the women farmer group